Evaluation Irrigation Institution Aspect in Rice Farming System on Banjarbaru, South Kalimantan - Mustaniroh, Siti Asmaul (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
This research is designed to evaluated institution aspect of irrigation in rice farming system. Methods of analysis use indicator value about physical condition (irrigation and drainage facilities), personal, treatment of irrigation system, and organization (P3A, PTGA). The result from analysis that condition in area is not good but enough to increase useful of water in area. For optimize of production rice farming system, developer of project must control irrigation system, so can be rehabilitate of irrigation and drainage facilities.Key words : evaluation, institution aspect of irrigation